Prospects of Organic Waste Management and the Significance of Earthworms - Kiyasudeen S, Katheem; Ibrahim, Mahamad Hakimi; Quaik, Shlrene; Ahmed Ismail, Sultan (Applied Environmental Science and Engineering for a Sustainable Future,, 2016)
The main aim of this book is to bridge the gap between aerobic and anaerobic waste treatments by concentrating on studies of earthworms. In particular, vermicomposting is being discussed as well as its properties and applications. Other subjects touch on the treatment of palm oil mill effluents, the various importance of earthworms, its scope and future aspects of earthworm research, and the impact of waste management practices on human health.